PENGARUH PEMBIAYAAN MUDHARABAH DAN PEMBIAYAAN MUSYARAKAH TERHADAP TINGKAT PROFITABILITAS BANK UMUM SYARIAH PERIODE 2016-2021 - Shauwa Safrizani; Harfandi (Jurnal Ekonomi dan Bisnis, 2023)
This study aims to determine the effect of mudharabah and musyarakah financing and to find out how the effect of mudharabah and musyarakah financing or both on ROE in Islamic commercial banks. This study uses secondary data in the form of annual financial reports at Islamic commercial banks for 2016- 2021 with research aids using Windows SPSS version 25.0. the population of this study is the total number of Islamic Commercial Banks registered with Bank Indonesia in 2021. In this study the samples were taken using the purposive sampling method, a total of 30 samples. Based on the research results obtained regarding the effect of mudharabah financing on ROE at Islamic Commercial Banks with the 2016-2021 research year, it has no significant effect. The effect of musyarakah financing on ROE at Islamic Commercial Banks has a significant effect. And the results of mudharabah and musyarakah financing have a positive significant effect on the level of profitability of Islamic commercial banks.